Electrodes from carbonized grass clippings for bioelectrochemical systems - Alexander Langsdorf; Michael Halim; Marianne Volkmar; Markus Stöckl; Ralf Harnisch; Peter Hahn; Roland Ulber; Dirk Holtmann (Cleaner Chemical Engineering, 2024)
One major obstacle to the commercialization of electrobiotechnological systems is the cost of materials, including expensive electrodes. Smart recycling as well as the use of renewable resources can contribute to producing electrodes more ecologically and economically. Green waste is a biogenic residual material that occurs mainly in urban areas and is currently not recycled to a sufficient extent. Here we show the fabrication of electrodes from carbonized grass clippings and their application in microbial electrosynthesis as well as microbial fuel cells. While the electrodes cannot compete with established metal competitors for water electrolysis in microbial electrosynthesis, they perform comparably to commercial graphite electrodes in microbial fuel cells. With Geobacter sulfurreducens, a current response can be recorded for more than six weeks. To the best of our knowledge, this is the first time that carbonized green waste has been used as an electrode material for bioelectrochemical systems. This demonstrates the potential of carbonized biological materials as a raw material for electrodes and presents a recycling alternative for green waste.